Strategi Peningkatan Layanan Bidang Hukum dan Penyelesaian Sanggah (BHPS) Lembaga Pengadaan Barang/Jasa Pemerintah (LKPP) di Daerah - Yayan Rudianto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2012)
LKPP is the only non department governmental institution that has the duty to develop and formulate procurement for goods and service government policy. Since there is a consideration to perform the task and function to be effective soon, LKPP establishes Deputy of Law and Protest Settlement. it is as a response for many problems, especially in region, namely: technical guidance problem, advocacy, protest settlement/protest appeal, law problem handling, and expert witness, so that raising question: what is the most suitable strategy to improve BHPS service in region? To answer this question, SWOT analysis is presented as a way to identify SWOT factors (Strengths, Weaknesses, Opportunities, Threats), and strategy depicting the best compatibility among the factors. The result of this analysis shows that the average respondent's answer inside GE matrix is on high quadrant, viewed from strength (4,184202) and mid quadrant from the part of Opportunities and Threats (3,741818). Therefore, the most suitable strategies used in improving BHPS service in region are: 1. selective growth, 2. aggressive investment, 3. maintaining position in other places